Informed Consent pada Kasus Kegawatdaruratan di Rumah Sakit Berdasarkan Undang-Undang No. 17 Tahun 2023 - Damayanti, Tamara; Darma Putra, Hendri; Yulia Anggraeni, Happy (UNES Law Review, 2024)
In medical procedures, doctors are required to obtain informed consent. However, in emergency situations, doctors are often faced with patients who are incompetent and the family is not present to ask for consent. This can lead to lawsuits. This study aims to analyze the implementation of informed consent in Indonesia based on Law No. 17 of 2023 and to determine the obstacles and solutions to these problems. The method used is a normative legal approach, namely a literature study as the main source of research with primary legal materials. The results of the analysis show that a doctor does not need to obtain informed consent in emergency cases as stated in Law No. 17 of 2023 concerning Health Article 293 paragraph (9) and the guarantee of legal protection for doctors from claims for compensation after providing first aid with the aim of saving lives and preventing disability as in Article 275 paragraphs (1) and (2). A doctor should not hesitate to give his best efforts in saving or preventing patient disability without prior consent for medical procedures. Because the doctor only provides an agreement of efforts (Inspaningverbintenis) and is exempt from claims for compensation if the doctor is in the process of helping the patient in an emergency case.